2020
DOI: 10.1021/acschemneuro.9b00677
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and Baicalein Act as Potent Antiamyloidogenic and Fibril Destabilizing Agents for SOD1 Fibrils

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that has been associated with the deposition of aggregates of superoxide dismutase 1 (SOD1). Effective therapeutics against SOD1 fibrillation is still an area of active research. Herein, we demonstrate the potential of two naturally occurring flavonoids (quercetin and baicalein) to inhibit fibrillation of wild-type SOD1 with the aid of a series of biophysical techniques. Our seeding experiments reveal that both of these flavonoids signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…In vitro tests showed that quercetin glycosides, namely quercitrin and quercetin 3-beta-d-glucoside, inhibit misfolding and aggregation of SOD1 A4V mutant [ 132 ]. A similar effect on aggregation was observed with quercetin and baicalein [ 133 ]. Furthermore, preventive administration of quercetin in rats reduced oxidative stress, defective mitochondria, and brain cell death caused by aluminium exposure [ 134 ].…”
Section: Therapeutic Potentials Of Polyphenols In Als/ftdsupporting
confidence: 73%
“…In vitro tests showed that quercetin glycosides, namely quercitrin and quercetin 3-beta-d-glucoside, inhibit misfolding and aggregation of SOD1 A4V mutant [ 132 ]. A similar effect on aggregation was observed with quercetin and baicalein [ 133 ]. Furthermore, preventive administration of quercetin in rats reduced oxidative stress, defective mitochondria, and brain cell death caused by aluminium exposure [ 134 ].…”
Section: Therapeutic Potentials Of Polyphenols In Als/ftdsupporting
confidence: 73%
“…Furthermore, ALS-associated mutations augment the fibrillation of SOD1 to different degrees (Furukawa et al, 2008 , 2010 ; Lang et al, 2012 ; Chan et al, 2013 ; Abdolvahabi et al, 2016 , 2017 ; McAlary et al, 2016 ), whereas some de novo mutations and PTMs have been shown to prevent (Abdolvahabi et al, 2015 ; Rasouli et al, 2017 ; Pokrishevsky et al, 2018 ) or enhance fibrillation (Shi et al, 2013 ). The Thioflavin-T assay has also been used to examine if SOD1 fibrillation can be lowered using chaperone proteins (Yerbury et al, 2013 ) or small molecules (Bhatia et al, 2015 , 2020 : Malik et al, 2019 ).…”
Section: In Vitro Models To Examine Proteostasis and Prion-lmentioning
confidence: 99%
“…In neuro-2a cells transiently transfected with 16Q huntingtin (Htt) and 150 Htt, querce-tin increases cell viability and clears the mHtt aggregates via the upregulation of UPS activity [155]. In addition, quercetin binds to the SOD1 dimer, then blocks its fibrillization, and reduces the cytotoxicity of SOD1 fibrils in ALS [156,157]. Emerging evidence indicates that the excessive accumulation of metal ions generates amounts of ROS levels and induces neurotoxicity, which favours the pathological process in various neurodegenerative diseases [158][159][160], while the treatment of quercetin improves the viability and inhibits the proinflammatory responses via inhibiting the production of ROS levels and its resultant apoptosis [161,162].…”
Section: Antineuroinflammation Antioxidative Stressmentioning
confidence: 99%